Controlled porosity alumina structures for ultra-precision hydrostatic journal bearings - Durazo-Cardenas, Isidro; Stephenson, D. J.; Corbett, John (American Ceramic Society, 2010)
A series of fine grade alumina powders has been used in combination with maize starch granules to produce porous structures for porous hydrostatic journal bearing applications. A comprehensive series of tests was conducted to characterize porosity in terms of density, pore size and permeability. Successful processing of quality journal bearing components has been demonstrated for preferred combinations of alumina size and starch content, using fixed processing parameters. The new porous ceramic bearings showed consistent and reproducible properties and are suitable for a wide range of higher precision engineering applications. The porous ceramic bearing processing route has also proved to be low cost and environmentally sound.
Keywords: Porous materials; permeability; pores/porosity; alumina